Nontuberculous mycobacterial pulmonary disease and associated risk factors in China: A prospective surveillance study. Issue 1 (July 2021) - Tan, Yaoju; Deng, Yunfeng; Yan, Xiaofeng; Liu, Fangchao; Tan, Yunhong; Wang, Quan; Bao, Xundi; Pan, Jianhua; Luo, Xiaolu; Yu, Yanhong; Cui, Xiaoli; Liao, Guangfu; et al.
Abstract: Background: We aimed to address the knowledge gap that exists regarding the epidemiological, demographic, and clinical characteristics of nontuberculous mycobacterial pulmonary diseases (NTM-PDs) among smear-positive patients with symptoms suggestive of pulmonary tuberculosis (PTB) in China. Methods: Prospective and national surveillance of NTM-PD was performed from 17 hospitals within the China Nontuberculous Mycobacteria Surveillance Study (CNTMS). Patients were eligible for inclusion if they had positive smears during hospitalization. Sputum specimens were collected for molecular species identification. Results: 6, 766 patients with valid results were included, consisting of 6, 236 (92.2%) with PTB, 458 (6.8%) with NTM-PD, and 72 (1.0%) with colonization. The proportion of NTM-PD in PTB patients exhibited significant geographic diversity, ranging from 3.2% in the northwest to 9.2% in the south. The most prevalent species was Mycobacterium intracellulare, followed by Mycobacterium abscessus complex. Females, elderly people, and patients with bronchiectasis or COPD are at high risk for developing NTM-PD, while patients with diabetes have a lower risk of NTM-PD when compared with non-diabetic patients. Regarding clinical symptoms, lower rates of persistent cough and weight loss were noted in NTM-PD patients than in PTB patients. Conclusions: Approximately one-fifteenth of PTB patients are afflicted with nontuberculous mycobacterial infections in China. The prevalence of NTM shows geographic diversity across the country, and it showed a gradual increase from north to south and from west to east. NTM-PD patients are prone to exhibit less severe clinical symptoms than PTB patients, highlighting the importance of raising awareness of NTM diseases to improve decision making on how to best screen, diagnose, and treat NTM in TB-endemic settings.